Income Convergence or Divergence in the Aftermath of the COVID-19 Shock? - Brussevich, Mariya (IMF Working Papers; Working Paper, 2022)
The paper extends the work of Deaton (2021) by exploring the period of post-crisis recovery in 2021-2024. The paper documents per-capita income divergence during the period of post-shock recovery, with countries at the bottom of the income distribution falling significantly behind. Findings suggest that higher COVID-19 vaccination rates and targeted virus containment measures are associated with faster recovery in per-capita incomes in the medium term. Evidence on the effectiveness of economic support policies for reducing cross-country income inequality, including fiscal and monetary policies, is mixed especially in the case of developing countries.